Successful Treatment of Actinic Keratosis with Kanuka Honey. (31st May 2018) - Mane, Saras; Singer, Joseph; Corin, Andrew; Semprini, Alex
Abstract : Actinic keratoses form as rough, scaly plaques on sun-exposed areas; they can be an important step in premalignant progression to squamous cell cancer of the skin. Currently, pharmacological treatments consist of topical immunomodulatory agents with poor side effect profiles. Use of honey has been common in both ancient and modern medicine, where it is now a key therapy in the management of wound healing. In vitro studies show the New Zealand native Kanuka honey to have immunomodulatory and antimitotic effects, with recent evidence suggesting efficacy of topical application in a variety of dermatological contexts, including rosacea and psoriasis. Here, we present a case report of a 66-year-old gentleman with an actinic keratosis on his hand, which had been present for years. Regular application of Kanuka honey over three months resulted in remission immediately following the treatment period with no signs of recurrence at nine months.